Improved Circulation in the Northern Hemisphere by Adjusting Gravity Wave Drag Parameterizations in Seasonal Experiments With ICON‐NWP. Issue 3 (11th March 2021) - Köhler, Raphael; Handorf, Dörthe; Jaiser, Ralf; Dethloff, Klaus; Zängl, Günther; Majewski, Detlev; Rex, Markus
Abstract: The stratosphere is one of the main potential sources for subseasonal to seasonal predictability in midlatitudes in winter. The ability of an atmospheric model to realistically simulate the stratospheric dynamics is essential in order to move forward in the field of seasonal predictions in midlatitudes. Earlier studies with the ICOsahedral Nonhydrostatic atmospheric model (ICON) point out that stratospheric westerlies in ICON are underestimated. This is the first extensive study on the evaluation of Northern Hemisphere stratospheric winter circulation with ICON in numerical weather prediction (NWP) mode. Seasonal experiments with the default setup are able to reproduce the basic climatology of the stratospheric polar vortex. However, westerlies are too weak and major stratospheric warmings too frequent in ICON. Both a reduction of the nonorographic, and a reduction of the orographic gravity wave and wake drag lead to a strengthening of the stratospheric vortex and a bias reduction, in particular in January. However, the effect of the nonorographic gravity wave drag scheme on the stratosphere is stronger. Stratosphere‐troposphere coupling is intensified and more realistic due to a reduced gravity wave drag. Furthermore, an adjustment of the subgrid‐scale orographic drag parameterization leads to a significant error reduction in the mean sea level pressure. As a result of these findings, we present our current suggested improved setup for seasonal experiments with ICON‐NWP. Plain Language Summary: Although seasonal forecasts for midlatitudes have the potential to be highly beneficial to the public sector, they are still characterized by a large amount of uncertainty. Exact simulations of the circulation in the stratosphere can help to improve tropospheric predictability on seasonal time scales. For this reason, we investigate how well the new German atmospheric model is able to simulate the stratospheric circulation. The model reproduces the basic behavior of the Northern Hemisphere stratospheric polar vortex, but the westerly circulation in winter is underestimated. The stratospheric circulation is influenced by gravity waves that exert drag on the flow. These processes are only partly physically represented in the model, but are very important and are hence parameterized. By adjusting the parameterizations for the gravity wave drag, the stratospheric polar vortex is strengthened, thereby yielding a more realistic stratospheric circulation. In addition, the altered parameterizations improve the simulated surface pressure pattern. Based upon this, we present our current suggested improved model setup for seasonal experiments. Key Points: Seasonal simulations with ICON‐NWP underestimate stratospheric vortex strength in winter Adjusted gravity wave drag schemes lead to reduced biases in Northern Hemisphere circulation Stratosphere‐troposphere coupling is intensified with a reduced gravity wave drag